The attenuation of hearing protectors against high-level shooting impulses - E. Toppila; J. Starck (Archives of Acoustics)
The acoustical attenuation of five different hearing protectors were investigated using real impulses and miniature microphone technique in field conditions from a 23 mm antiaircraft cannon, from 122 mm howitzer and from an explosion of 1 kg of TNT. The measurements were carried out using voluntary military officers exposed to similar impulses in their work. The combination of earmuffs and earplugs proved to give the best attenuation. The attenuation of the earmuffs was related to the size of the cup. Light protectors gave practically no protection against the highest impulses from howitzer and TNT-blasts.